Differential Effect of Smoking on Gene Expression in Head and Neck Cancer Patients - Alexandra Iulia Irimie (International Journal of Environmental Research and Public Health, 2018)
Smoking is a well-known behavior that has an important negative impact on human health, and is considered to be a significant factor related to the development and progression of head and neck squamous cell carcinomas (HNSCCs). Use of high-dimensional datasets to discern novel HNSCC driver genes related to smoking represents an important challenge. The Cancer Genome Atlas (TCGA) analysis was performed in three co-existing groups of HNSCC in order to assess whether gene expression landscape is affected by tobacco smoking, having quit, or non-smoking status. We identified a set of differentially expressed genes that discriminate between smokers and non-smokers or based on human papilloma virus (HPV)16 status, or the co-occurrence of these two exposome components in HNSCC. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways classification shows that most of the genes are specific to cellular metabolism, emphasizing metabolic detoxification pathways, metabolism of chemical carcinogenesis, or drug metabolism. In the case of HPV16-positive patients it has been demonstrated that the altered genes are related to cellular adhesion and inflammation. The correlation between smoking and the survival rate was not statistically significant. This emphasizes the importance of the complex environmental exposure and genetic factors in order to establish prevention assays and personalized care system for HNSCC, with the potential for being extended to other cancer types.